Every color of light - Osada, Hiroshi, 1939-2015 (Enchanted Lion Books, 2020)
Illustrations and easy-to-read, rhyming text depict nature darkened by a brief rainstorm then, at sunset, colors brighten, rain drips like crystals, and the bright white moon shines as we fall asleep.